A Longitudinal and Multidimensional Examination of the Associations Between Temperament and Self‐Restraint During Toddlerhood. Issue 6 (22nd October 2018) - Smith Watts, Ashley K.; Friedman, Naomi P.; Corley, Robin P.; Hewitt, John K.; Hink, Laura K.; Robinson, JoAnn L.; Rhee, Soo H.
Abstract : Developing self‐restraint, or the inhibition of behavior in response to a prohibition, is an important process during toddlerhood. The objective of this study was to gain a better understanding of individual differences in the development of self‐restraint during toddlerhood by examining stable elements and growth of temperament (i.e., attentional control, behavioral inhibition, negative emotionality), general intelligence, and self‐restraint. Participants were 412 same‐sex twin pairs (approximately 90% European American) from predominately middle‐class households in Colorado. Data were collected at 14, 20, 24, and 36 months. Results indicated that higher behavioral inhibition, attentional control, and intelligence were independently associated with better self‐restraint, whereas higher negative emotionality was an independent predictor of lower self‐restraint. The associations between temperament and self‐restraint generally appeared to be stable from 14 to 36 months.